One-step photonic curing of screen-printed conductive Ni flake electrodes for use in flexible electronics - (:unkn) unknown (NATURE PORTFOLIO, 2021)
Photonic curing has shown great promise in maintaining the integrity of flexible thin polymer substrates without structural degradation due to shrinkage, charring or decomposition during the sintering of printed functional ink films in milliseconds at high temperatures. In this paper, single-step photonic curing of screen-printed nickel (Ni) electrodes is reported for sensor, interconnector and printed electronics applications. Solid bleached sulphate paperboard (SBS) and polyethylene terephthalate polymer (PET) substrates are employed to investigate the electrical performance, ink transfer and ink spreading that directly affect the fabrication of homogeneous ink films. Ni flake ink is selected, particularly since its effects on sintering and rheology have not yet been examined. The viscosity of Ni flake ink yields shear-thinning behavior that is distinct from that of screen printing. The porous SBS substrate is allowed approximately 20% less ink usage. With one-step photonic curing, the electrodes on SBS and PET exhibited electrical performances of a minimum of 4 Omega /sq and 16 Omega /sq, respectively, at a pulse length of 1.6 ms, which is comparable to conventional thermal heating at 130 degrees C for 5 min. The results emphasize the suitability of Ni flake ink to fabricate electronic devices on flexible substrates by photonic curing.
Keywords: SINTERING PROCESS; COPPER; NANOPARTICLES; TRANSPARENT; PERFORMANCE; FABRICATION; COMPOSITE; MECHANISM; SUBSTRATE; GRAPHENE